Interactive Spaced Online Education in Pediatric Trauma. (June 2016) - Shenoi, Rohit; Rubalcava, Daniel; Naik-Mathuria, Bindi; Sloas, Harold A.; Delemos, David; Xu, Linzhi; Mendez, Donna
Pediatric resident trauma education is suboptimal due to lack of a curriculum and limited trauma experience and education resources. The objective of the study was to test knowledge retention and acceptability of interactive spaced education (ISE) in pediatric trauma. Prospective, randomized trial involving 40 physicians in a pediatric emergency department was used. Instrument was comprised of 48 multiple-choice questions (evaluative component) and answer critiques (educational component) on pediatric trauma divided into two modules. The instrument was assessed for test–retest reliability, item difficulty, and construct validity. Intervention consisted of online administration of each module as eight spaced emails (3 questions each) over a course of 4 weeks and was repeated after 2 and 4 months. Participants received an answer critique on committing to an answer. Primary outcome was difference in mean percentage of correct answers at 2 and 4 months versus baseline. Paired t test and effect size (d) were performed. Secondary outcome was exit-survey of ISE acceptability. There was significant improvement at 2 months (8.0, 95% confidence intervel [CI] = [3.6, 12.5], d = 0.75), but improvement at 4 months (1.6, 95% CI = [−4.5, 7.7], d = 0.18) was not significant. Sixty percent would retake and recommend ISE to others. Interactive, spaced education improves knowledge in pediatric trauma and is well accepted. Studies are required to determine the optimal spacing interval for this form of education.